LOCALLY-ADVANCED BREAST CANCER IN A MALE PATIENT: A CASE REPORT - Jakupi, Nedjati; Velkov, Stojan; Despotovski, Despot; Atanasova, Ljubica (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Male breast cancer is a rare pathology, representing 1% of the cases of breast cancer, and less than 1% of all cancers in men. It tends to be diagnosed at a later stage, and also at an older age, the mean being 67 years old. Little is known about the etiology of the disease, and the treatment approach is usually the same as in female breast cancer. We hereby present a case of a 63 year old man with a locally-advanced breast cancer, complicated by skin ulcerations. The aim of this paper is to contribute to raising awareness for the disease and point out the fact that breast cancer behaves different in male patients. Keywords: ulcerated, breast, cancer, male, mastectomy.